Study of the Mechanism of Action of Guanxin Shutong Capsules in the Treatment of Coronary Heart Disease Based on Metabolomics - Wang, Dan; Shi, Chang; Ge, Zhen-Hua; Wei, Yu-Xi; Liu, Tian-Tian; Wang, Yue; Zhou, Xin-Feng; Yang, Zi-Jun; Wang, Wei-Ting; Zhang, Yan-Wen; Zhu, Xue-Hui; Zhang, Jun; et al. (Frontiers in Pharmacology, 2021)
Background: Guan-Xin-Shu-Tong capsule (GXSTC) is a traditional Chinese medicine (TCM) that has been used to treat coronary heart disease (CHD) for many years in China. However, the holistic mechanism of GXSTC against CHD is still unclear. Therefore, the purpose of this paper was to systematically explore the mechanism of action GXSTC in the treatment of CHD rats using a metabolomics strategy. Methods: A CHD model was induced by ligation of the left anterior descending coronary artery (LAD). In each group, echocardiography was performed; the contents of creatine kinase (CK), lactate dehydrogenase (LDH) and aspartate transaminase (AST) in serum were determined; and the myocardial infarct size was measured. The metabolites in plasma were analyzed by UHPLC-MS/MS-based untargeted metabolomics. Then, multivariate statistical analysis was performed to screen potential biomarkers associated with the GXSTC treatment in the LAD-induced rat CHD model. Finally, the MetaboAnalyst 4.0 platform was used for metabolic pathway enrichment analysis. Results: GXSTC was able to regulate the contents of CK, LDH and AST; restore impaired cardiac function; and significantly reduce the myocardial infarction area in model rats. Twenty-two biomarkers and 9 metabolic pathways of GXSTC in the treatment of CHD were identified through UHPLC-MS/MS-based untargeted metabolomics analysis. Conclusion: GXSTC regulates metabolic disorders of endogenous components in LAD-induced CHD rats. The anti-CHD mechanism of GXSTC is mainly related to the regulation of amino acid, lipid and hormonal metabolism. This study provides an overall view of the mechanism underlying the action of GXSTC against CHD.